Comparison of the efficacy of vocal training and vocal microsurgery in patients with early vocal fold polyp - Wang,Hanqing (2019)
Abstract Introduction: Vocal fold polyp is a benign proliferative disease in the superficial lamina propria of the vocal fold, and vocal microsurgery can improve the voice quality of patients with vocal fold polyp. In preliminary studies, we found that vocal training could improve the vocal quality of patients with early vocal fold polyp. Objective: This study aimed to compare the efficacies of vocal training and vocal microsurgery in patients with early vocal fold polyp. Methods: A total of 38 patients with early vocal fold polyp underwent 3 months of vocal training (VT group); another 31 patients with early vocal fold polyp underwent vocal microsurgery (VM group). All subjects were assessed using laryngostroboscopy, voice handicap index, and dysphonia severity index, and the efficacies of vocal training and vocal microsurgery were compared. Results: The cure rates of vocal training and vocal microsurgery were 31.6% (12/38) and 100% (31/31), respectively. The intragroup paired-sample t-test showed that the post treatment vocal handicap index, maximum phonation time, highest frequency (F0-high), lowest intensity (I-low), and dysphonia severity index in both the VT and VM groups were better than those before treatment, except for the jitter value. The intergroup independent-sample t-test revealed that the emotional values of vocal handicap index (t = − 2.22, p = 0.03), maximum phonation time (t = 2.54, p = 0.013), jitter (t = − 2.11, p = 0.03), and dysphonia severity index (t = 3.24, p = 0.002) in the VT group were better than those in the VM group. Conclusions: Both, vocal training and vocal microsurgery could improve the voice quality of patients with early vocal fold polyp, and these methods present different advantages.